1996
DOI: 10.1172/jci118763
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a subnormal vitamin B-6 status on homocysteine metabolism.

Abstract: Homocysteine, an atherogenic amino acid, is either remethylated to methionine or metabolized to cysteine by the transsulfuration pathway. The biochemical conversion of homocysteine to cysteine is dependent upon two consecutive, vitamin B-6-dependent reactions.To study the effect of a selective vitamin B-6 deficiency on transsulfuration, we performed oral methionine load tests on 22 vitamin B-6-deficient asthma patients treated with theophylline (a vitamin B-6 antagonist) and 24 age-and sex-matched controls wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
112
2
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(132 citation statements)
references
References 50 publications
(48 reference statements)
12
112
2
6
Order By: Relevance
“…Previous studies have reported increased cystathionine concentrations in patients with asthma, a condition known to be related to systemic inflammation 29. Accordingly, in our study, plasma cystathionine concentration was directly associated with CRP, a marker of inflammation 30.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies have reported increased cystathionine concentrations in patients with asthma, a condition known to be related to systemic inflammation 29. Accordingly, in our study, plasma cystathionine concentration was directly associated with CRP, a marker of inflammation 30.…”
Section: Discussionsupporting
confidence: 63%
“…Alternatively, high plasma cystathionine may reflect suboptimal nutritional status 20, 21. In this regard, previous studies showed that low serum concentrations of B‐vitamins, in particular vitamin B6, were strongly associated with high cystathionine levels 21, 29. However, any influence by poor nutrition status seems unlikely, because plasma levels of B‐vitamins neither attenuated the association between plasma cystathionine and stroke events nor introduced any significant effect modification.…”
Section: Discussionmentioning
confidence: 98%
“…A possible explanation has been attributed to the role of Sadenosylmethionine in the regulation of homocysteine metabolism. S-adenosylmethionine (an activator for the enzyme cystathionine b-synthase) favors folate and vitamin B 12 -dependent homocysteine remethylation to methionine in the fasting state; vitamin B 6 deficiency does not affect Sadenosylmethionine Ubbink et al, 1996). Homocysteine is only directed to the trans-sulfuration pathway when methionine is in excess.…”
Section: Discussionmentioning
confidence: 99%
“…In certain studies, interlaboratory imprecision with immunoassay methods has been reported. 21 In addition, fluorescence immunoassay reagents are relatively very expensive. 15 As stated by Refsum et al in their comprehensive 2004 review coauthored by a group of the world's leading experts in this field, many analytical methods afford results that do not fulfill baseline bias and imprecision criteria.…”
Section: Homocysteine and Cysteine In Human Healthmentioning
confidence: 99%